2017
DOI: 10.1007/s13197-017-2726-1
|View full text |Cite
|
Sign up to set email alerts
|

Alginate edible films containing microencapsulated lemongrass oil or citral: effect of encapsulating agent and storage time on physical and antimicrobial properties

Abstract: Active edible films have been proposed as an alternative to extend shelf life of fresh foods. Most essential oils have antimicrobial properties; however, storage conditions could reduce their activity. To avoid this effect the essential oil (EO) can be microencapsulated prior to film casting. The aim of this study was to determine the effects of the type of encapsulating agent (EA), type of EO and storage time on physical properties and antimicrobial activity of alginate-based films against ATCC 25922. Trehalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
(45 reference statements)
1
17
0
Order By: Relevance
“…Thus, film opacity was evaluated by detecting the light transmission at 600 nm through the CH films containing different amounts of BEOMCs. Figure 6 shows that film opacity was significantly increased, more than doubling, in the films containing even only 1% (6.7 ± 0.08 mm −1 ) of microcapsules compared to the control samples (3.1 ± 0.07 mm −1 ), confirming previous studies that have demonstrated that film transparency decreased in all the films prepared in the presence of either nanoparticles or microcapsules [ 29 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 84%
“…Thus, film opacity was evaluated by detecting the light transmission at 600 nm through the CH films containing different amounts of BEOMCs. Figure 6 shows that film opacity was significantly increased, more than doubling, in the films containing even only 1% (6.7 ± 0.08 mm −1 ) of microcapsules compared to the control samples (3.1 ± 0.07 mm −1 ), confirming previous studies that have demonstrated that film transparency decreased in all the films prepared in the presence of either nanoparticles or microcapsules [ 29 , 50 , 51 ].…”
Section: Resultssupporting
confidence: 84%
“…Ultraviolet-visible (UV-Vis) absorption spectra of prepared microcapsules supernatants were recorded by UV-Vis spectrophotometry (SPECORD plus 50, Jena Analytical Instruments AG, Germany) over wavelengths ranging from 200 to 500 nm [24]. IR spectra of microcapsules were acquired using FTIR (VERTEX 70, Bruker, Germany) with a buckled KBr sheet in the spectral range of 400 to 4000 cm −1 ; an average of 32 scans were recorded at a resolution of 4 cm −1 .…”
Section: Characterizations Of Microcapsulesmentioning
confidence: 99%
“…During recent years, the interest in the bio-efficacy of essential oils and their uses as natural antimicrobials in environmentally friendly products has rapidly increased. Several authors have reported on innovations in smart packaging food systems based on essential oils [35][36][37][38][39][40][41]. Among essential oils, the oil obtained from lemongrass plants of genus Cymbopogon, particularly of C. citratus (CAS RN 8000-29-1) known as citronella or lemongrass oil, has been studied and used due to its broad-spectrum antimicrobial activity, pleasant aroma and uses in food, pharmaceutical and cosmetic products, as well as in mosquito repellents and natural pesticides.…”
Section: Microencapsulated Antimicrobial Essential Oilsmentioning
confidence: 99%